2020
DOI: 10.1093/rb/rbz052
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans aspects of binary titanium alloys for biomedical applications

Abstract: Titanium and its alloys are widely used in biomedical devices, e.g. implants, due to its biocompatibility and osseointegration ability. In fact, fungal (Candida spp.) infection has been identified as one of the key reasons causing the failure of the device that is inevitable and impactful to the society. Thus, this study evaluated the surface morphology, surface chemical composition and Candida albicans adhesion on specimens of 16 binary Ti-alloys (∼5 wt% of any one of the alloy elements: Ag, Al, Au, Co, Cr, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Nonetheless, it should be noted that this proof-of-concept study only showed the UV-treated titanium surface can be coated with various percentages of PHMB and retained for certain time, which could be a strategy for maintaining a low occurrence of F. nucleatum and possibly preventing re-infection on the titanium. This kind of easy self-assembled coating can also be applied to different titanium-based medical applications, such as orthodontics [42,43], dentofacial orthopaedics [44,45], and other implant medical devices [5] that are prone to infection. This variety of applications might need different concentrations for the optimal application of PHMB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it should be noted that this proof-of-concept study only showed the UV-treated titanium surface can be coated with various percentages of PHMB and retained for certain time, which could be a strategy for maintaining a low occurrence of F. nucleatum and possibly preventing re-infection on the titanium. This kind of easy self-assembled coating can also be applied to different titanium-based medical applications, such as orthodontics [42,43], dentofacial orthopaedics [44,45], and other implant medical devices [5] that are prone to infection. This variety of applications might need different concentrations for the optimal application of PHMB.…”
Section: Discussionmentioning
confidence: 99%
“…Although titanium is considered an ideal material for implant dentistry and other implantable medical devices [5], implant failure still occurs [6]. One of the major reasons for failure is infections caused by bacteria, such as peri-implantitis [7].…”
Section: Introductionmentioning
confidence: 99%
“…To prevent infection and ensure high success rates in clinical applications of medical devices and implants made from Ti-Zr alloys, antimicrobial performance should be improved. Chen et al (2020) confirmed that Ti-Zr has a lower occurrence of Candida Albicans (C. Albicans) which might be clinically advantageous for medical devices, but the antibacterial mechanism still needs to be explored. To further improve the antibacterial properties of Ti-Zr alloys, adding antibacterial elements like Cu to improve their antibacterial properties is a good choice.…”
Section: Ti-zr-cu Alloysmentioning
confidence: 94%
“…Cell culture experiments on osteoblast cells with Ti–5Nb– x Fe alloys showed that the rate of cell proliferation is related to the amount of Fe and the chemical bonding between Fe and cells and that Fe with specific ratio has good biocompatibility [ 199 ]. The ranking of elements added to Ti in bioimplants regarding their cell viability enhancing effect, from lowest to highest, is Cu < Al < Ag < V < Mn < Cr < Zr < Nb < Mo < Cp-Ti, and that regarding their cytotoxicity is Cp-Ti < Sn < Ta < Mo < Nb < Zr < Cr < Mn < V < Ag < Ni = Al < Cu [ 200 204 ].…”
Section: Advanced Manufacturing (Am) Of Titanium Alloys For Biomedical Applicationmentioning
confidence: 99%